Challenges that influence the implementation of the Saudi Central Board for Accreditation of Healthcare Institutions (CBAHI) Standards in Hospitals - Alsaigh, B. A.; Soehod, K.; Ahmad, S. (International Journal of Psychosocial Rehabilitation, 2020)
The Central Board for Accreditation of Healthcare Institutions (CBAHI) Saudi Arabia was established in 2005 to implement the quality standards in order to improve the quality of care in all Saudi hospitals across the country. It is worth mentioning that quality is a major concern in Saudi hospitals.Therefore, the Saudi government has adopted Total Quality Managment (TQM) framework as a significant component of its Saudi 2030 vision. The interest in accreditation is growing in the Middle East, but the studies are rare about the challenges that influence the implementation of the CBAHI standards in hospitals. This study aims to investigate the factors in TQM perspective that influence the implementation of Saudi CBAHI accreditation standards in health-care sector by case study based on qualitative method. This research attempts to bridge the gap, helping professionals and policy makers in Saudi healthcare sector to implement CBAHI standards. This study will guide the hospitals to sustain the improvements for implementation of TQM and accreditations standards.